PLEIOTROPY IN THE WILD: THE DORMANCY GENE DOG1 EXERTS CASCADING CONTROL ON LIFE CYCLES. (16th November 2012) - Chiang, George C. K.; Barua, Deepak; Dittmar, Emily; Kramer, Elena M.; de Casas, Rafael Rubio; Donohue, Kathleen
<x xml:space="preserve">Abstract</x> In the wild, organismal life cycles occur within seasonal cycles, so shifts in the timing of developmental transitions can alter the seasonal environment experienced subsequently. Effects of genes that control the timing of prior developmental events can therefore be magnified in the wild because they determine seasonal conditions experienced by subsequent life stages, which can influence subsequent phenotypic expression. We examined such environmentally induced pleiotropy of developmental‐timing genes in a field experiment with Arabidopsis thaliana. When studied in the field under natural seasonal variation, an A. thaliana seed‐dormancy gene, Delay Of Germination 1 (DOG1), was found to influence not only germination, but also flowering time, overall life history, and fitness. Flowering time of the previous generation, in turn, imposed maternal effects that altered germination, the effects of DOG1 alleles, and the direction of natural selection on these alleles. Thus under natural conditions, germination genes act as flowering genes and potentially vice versa. These results illustrate how seasonal environmental variation can alter pleiotropic effects of developmental‐timing genes, such that effects of genes that regulate prior life stages ramify to influence subsequent life stages. In this case, one gene acting at the seed stage impacted the entire life cycle.